THE INFLUENCE OF PRODUCTION COST MANAGEMENT MANAGEMENT MODEL ON IMPROVING THE ECONOMY OF IRON SMITH CRAFTSPEOPLE IN PUA SUNGAI DISTRICT - Tri Yuliani (Tamwil, 2023)
This study discusses the influence of the production cost management model on increasing the income of the blacksmith craftsmen in Nagari Sungai Pua, Sungai Pua District, Agam Regency. The purpose of this research is to find out the amount of costs incurred by the craftsmen every quarter and to find out how much income the blacksmith craftsmen earn each quarter. This type of research that the authors do is quantitative research. The population in this study were all 162 blacksmith industries in Nagari Sungai Pua. As for the results of the research that the author did, the effect of costs on the income of blacksmith craftsmen in Kenagarian Sungai Pua, Sungai Pua Subdistrict, Agam Regency, was that the total costs and income fluctuated every quarter, but at the end of 2010 the income of blacksmith craftsmen experienced a very drastic decrease while the costs incurred issued is getting bigger and bigger. Furthermore, by using the Fcount analysis where the Fcount of 9.285 is greater than the Ftable of 9.07, then Ho is accepted and Ho is rejected. And lastly, by using the Tcount value of the raw material variable cost of 1.696, while the T table is 1.646, it means that Ha is accepted and Ho is rejected. The Tcount value of the labor cost variable is 0.628, while Ttable is 0.675, meaning that Ha is rejected and Ho is accepted. The value of T counts for factory overhead costs is 4.342 while Ttable is 4.015, meaning that Ha is accepted and Ho is rejected.